Inhibition of the In Vitro Growth of Colletotrichum sp. the Cause of Anthracnose on Avocado Fruit by Yeast - Hartati, Sri; Rahmah, Syifa Aulia; Nasahi, Ceppy (CROPSAVER, 2025)
Anthracnose caused by Colletotrichum sp. is a major disease on  avocado fruit. An alternative to control this post harvest disease is by using biocontrol agents, such as yeasts. The research was objected to test the abilities of three yeast isolates i.e. Aureobasidium pullulans Dmg 11 DEP, Rhodotorulla minuta Dmg 16 BE and Candida tropicalis Lm 13 BE, to inhibit the in vitro growth of Colletotrichum sp. The experiment was arranged in the completely randomized design consisting of five treatments that were repeated four times each. The treatments were dual culture and double dish system of the culture of Colletotrichum sp. vs the yeast isolates as follow A. pullulans Dmg 11 DEP, R. minuta Dmg 16 BE, C. tropicalis Lm 13 BE, fungicide mancozeb, and a control. The results showed that the three yeast isolates were able to inhibit the colony growth of Colletotrichum sp. by 19,9% – 56,10%  on the dual culture and 15,56% – 26,08% on the double dish system. The yeasts caused abnormal growth of the Colletotrichum sp. hyphae, such as swollen, curly, rolled, and lysis. A. pullulans Dmg 11 DEP caused the highest inhibition, with the category of strong antifungal activity on dual culture, and moderate on double dish system.  It was concluded that the three yeast isolates have the ability to inhibit the in vitro growth of Colletotrichum sp. the caused of  anthracnose on avocado fruit.